6 pulse GTO thyristor converter simulation - Mohamad Fadzli, Abdul Rahman (2009)
Nowadays, the development of a large capacity Gate Turn Off (GTO) thyristor has made it possible to manufacture self-commutated converter employing GTO thyristor for power applications. This project focused on the design of GTO thyristor model by using PSPICE, the analysis of switching waveform of GTO thyristor and the implementation of GTO thyristor as a control element in 6 pulse converter circuit. This project also includes the explanations of the settings of operation condition and gate circuit parameters including firing angle and time delay of turn-on and turn-off pulses. Simulation results of dc output voltage are compared with mathematical calculation results, and it is shown that almost similar characteristics curves are obtained.